Yield of grain, forage and forage quality of new corn hybrids from High Valleys - Velasco Macias, Saúl; Tadeo Robledo, Margarita; Espinosa Calderón, Alejandro; Zaragoza Esparza, Joob; Canales Islas, Enrique; Coutiño Estrada, Bulmaro (Revista Mexicana de Ciencias Agrícolas, 2022)
In the Faculty of Higher Studies Cuautitlán (FESC-UNAM) and in the National Institute of Forestry, Agricultural and Livestock Research (INIFAP), there are hybrids in experimental phase or recent release for the High Valleys of Mexico, which are competitive with existing commercial hybrids. In this research, 10 corn hybrids were evaluated in two localities and in one of them with two sowing dates; that is; three different evaluation environments in the State of Mexico, in each environment two experiments were established with the 10 genotypes, in the first the objective was to determine the grain productivity and in the second they were to determine the productivity and quality of forage. A randomized complete block experimental design with 10 genotypes and three repeats was used, the statistical analysis was performed with a factorial arrangement, which considered the 10 hybrids and three environments, as well as the genotype x environment interaction. In the conclusions it was determined that the hybrid Atziri Puma presented the highest grain yield (8 044 kg ha-1), followed by the hybrid Tsíri Puma (7 783 kg ha-1), both recently released commercially by FES Cuautitlán, UNAM. The hybrid Tlaoli Puma had the highest yield of green forage (70 202 kg ha-1). In forage quality analyses, no significant differences between hybrids were observed. Atziri puma, Tlaoli puma and Tsiri puma already have their registration with the National Catalog of Plant Varieties (CNVV) and Breeder’s Title.
Keywords: Zea mays; corn; forage quality; genotypes; grain yield; productivity